Preparation and characterization of polyelectrolyte-coated gold nanoparticles - Dorris, Annie (Langmuir : the ACS journal of surfaces and colloids, 2008)
Gold nanoparticles of 5 nm diameter, stabilized by 4-(dimethylamino)pyridine (DMAP), were coated with poly(sodium 4-styrene sulfonate) (PSS) via electrostatic self-assembly. The suspension stability, monitored by the gold surface plasmon band (SPB), was studied by varying the pH, the PSS chain length, and PSS concentration. Enhanced stability is obtained at pH 10 (above the pKa of DMAP) when the polymer chain length matches or exceeds the particle circumference. Solid state 13C NMR was used to determine the presence of DMAP and polymers after subsequent deposition of weak and strong polycations: poly(allylamine hydrochloride) (PAH) and poly(diallyldimethylammonium chloride) (PDADMAC). At pH 10, DMAP remains associated with the nanoparticle after the first PSS layer has been formed. When PAH or PDADMAC are subsequently added at pH 4.5, DMAP is expelled, the suspensions remain stable, and zeta potential values indicate complete charge reversal. In the case of PDADMAC, however, the first layer of PSS is not fully retained. When PDADMAC is added at pH 10, DMAP and the first PSS layer are retained but lower zeta potentials and a higher SPB shift indicate a degraded stability. For PAH addition at pH 9.5, both DMAP and PSS are expelled and the suspension becomes unstable. These differences in stability of the multilayer components and the nanoparticle suspension are rationalized in terms of chain flexibility, polymer charge density, and the ability of the polymer functional groups to directly interact with the gold surface